Abnormal Aortic Wall Properties in Women with Turner Syndrome - Bons, Lidia R.; Van Den Hoven, Allard T.; Malik, Maira; Van Den Bosch, Annemien E.; McGhie, Jacky S.; Duijnhouwer, Anthonie L.; Siebelink, Hans-Marc J.; Hirsch, Alexander; Devos, Daniel H.; Rietzschel, Ernst; von der Thüsen, Jan H.; van de Laar, Ingrid M.B.H.; Verhagen, Judith M.A.; van der Pluijm, Ingrid; Budde, Ricardo P.J.; Roos-Hesselink, Jolien W. (AORTA, 2020)
Background Turner syndrome (TS) is associated with aortic dilatation and dissection, but the underlying process is unclear. The aim of this study was to investigate the elastic properties and composition of the aortic wall in women with TS.Methods In this cross-sectional study, 52 women with TS aged 35 ± 13 years (50% monosomy, 12 with bicuspid aortic valve [BAV] and 4 with coarctation) were investigated using carotid-femoral pulse wave velocity (CF-PWV) by echocardiography and ascending aortic distensibility (AAD) and aortic arch pulse wave velocity (AA-PWV) by magnetic resonance imaging (MRI). As control group, 13 women with BAV without TS and 48 healthy patients were included.Results Women with TS showed a higher AA-PWV (β = 1.08, confidence interval [CI]: 0.54–1.62) after correcting for age and comorbidities compared with controls. We found no significant difference in AAD and CF-PWV. In women with TS, the presence of BAV, coarctation of the aorta, or monosomy (45, X) was not associated with aortic stiffness. In addition, aortic tissue samples were investigated with routine and immunohistochemical stains in five additional women with TS who were operated. The tissue showed more compact smooth muscle cell layers with abnormal deposition and structure of elastin and diminished or absent expression of contractile proteins desmin, actin, and caldesmon, as well as the progesterone receptor.Conclusion Both aortic arch stiffness measurements on MRI and histomorphological changes point toward an inherent abnormal thoracic aortic wall in women with TS.
Keywords: Turner syndrome; aortic stiffness; pulse wave velocity; echocardiography; cardiovascular magnetic resonance